The effect of 4-week training period on plasma neuropeptide Y, leptin and ghrelin responses in male rowers - Rämson, R.; Jürimäe, J.; Jürimäe, T.; Mäestu, J. (European Journal of Applied Physiology, 2012)
The aim was to investigate the effect of high-volume low intensity resistance training protocol combined with endurance training on plasma neuropeptide Y (NPY) concentration in rowers. Additionally, leptin and ghrelin, as markers for body energy balance concentrations, were monitored. 12 highly trained national and international level male rowers participated in this study. The participants were tested three times—after reference week (T1), after 2 weeks of high-volume training (T2) and after a recovery week (T3) for aerobic performance, energy intake and expenditure, and blood biochemical parameters. The submaximal rowing performance decreased significantly (P = 0.019) at T2. Fasting leptin decreased significantly (from 2.05 ± 0.88 to 1.28 ± 0.53 ng/mL; P = 0.009) at T2 and increased significantly (from 1.28 ± 0.53 to 1.79 ± 0.79 ng/mL; P = 0.002) at T3. Fasting ghrelin decreased significantly (from 980 ± 300.2 to 873.35 ± 198.6 pg/mL; P = 0.036) at T3 compared to T2, while no changes were found in fasting NPY. Significant decreases in exercise-induced leptin were observed at T2 (from 1.13 ± 0.5 to 1.08 ± 0.5 ng/mL; P = 0.012), PRE and POST test leptin values at T2 were significantly decreased compared to T1(1.40 ± 0.9 to 1.13 ± 0.5 and 1.44 ± 0.8 to 1.08 ± 0.5, respectively). Acute exercise-induced increases in NPY were found at T2 (from 128.1 ± 23.2 to 155.1 ± 28.9 pmol/L; P = 0.002) and at T3 (from 131.3 ± 20.5 to 159.7 ± 32.8 pmol/L, P = 0.004). In conclusion, the combination of high-volume training protocol and energy imbalance induces significant post-exercise changes in NPY, leptin, and ghrelin concentrations and decreases fasting leptin.